FRET-based genetically encoded sensors allow high-resolution live cell imaging of Ca2+ dynamics - Krebs, Melanie; Schumacher, Karin (The plant journal, 2012)
Temporally and spatially defined calcium signatures are integral parts of numerous signalling pathways. Monitoring calcium dynamics with high spatial and temporal resolution is therefore critically important to understand how this ubiquitous second messenger can control diverse cellular responses. Yellow cameleons (YCs) are fluorescence resonance energy transfer (FRET)-based genetically encoded Ca2+ -sensors that provide a powerful tool to monitor the spatio-temporal dynamics of Ca2+ fluxes. Here we present an advanced set of vectors and transgenic lines for live cell Ca2+ imaging in plants. Transgene silencing mediated by the cauliflower mosaic virus (CaMV) 35S promoter has severely limited the application of nanosensors for ions and metabolites and we have thus used the UBQ10 promoter from Arabidopsis and show here that this results in constitutive and stable expression of YCs in transgenic plants. To improve the spatial resolution, our vector repertoire includes versions of YCs that can be targeted to defined locations. Using this toolkit, we identified temporally distinct responses to external ATP at the plasma membrane, in the cytosol and in the nucleus of neighbouring root cells. Moreover analysis of Ca2+ dynamics in Lotus japonicus revealed distinct Nod factor induced Ca2+ spiking patterns in the nucleus and the cytosol. Consequently, the constructs and transgenic lines introduced here enable a detailed analysis of Ca2+ dynamics in different cellular compartments and in different plant species and will foster novel approaches to decipher the temporal and spatial characteristics of calcium signatures.